2015
DOI: 10.1111/hel.12216
|View full text |Cite
|
Sign up to set email alerts
|

Animal Model Reveals Potential Waterborne Transmission of Helicobacter pylori Infection

Abstract: We offer proof that H. pylori in water is infectious in mice, suggesting that humans drinking contaminated water may be at risk of contracting H. pylori infection. Much work needs to be performed to better understand the risk of infection from drinking H. pylori-contaminated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Our inability to cause infection was surprising, given the known capacity of this strain to successfully infect mice,26, 32 our wide range of exposure scenarios, and our previously published study that showed that SS1 in water could infect mice in a dose‐dependent manner 20. In our previous study, 4 weeks of exposure to water spiked with 10 9  CFU/L, 10 8  CFU/L 10 7  CFU/L, and 10 6  CFU/L of H. pylori caused infection in 39 of 40, 33 of 40, four of 38, and one of 40 mice, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our inability to cause infection was surprising, given the known capacity of this strain to successfully infect mice,26, 32 our wide range of exposure scenarios, and our previously published study that showed that SS1 in water could infect mice in a dose‐dependent manner 20. In our previous study, 4 weeks of exposure to water spiked with 10 9  CFU/L, 10 8  CFU/L 10 7  CFU/L, and 10 6  CFU/L of H. pylori caused infection in 39 of 40, 33 of 40, four of 38, and one of 40 mice, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a risk model of waterborne H. pylori infection using a quantitative microbial risk assessment methodology22 did not consider the VBNC form of H. pylori . Likewise, our recent study showing that constant exposure to the viable, cultural form of H. pylori in drinking water can infect mice did not account for exposure to the VBNC form 20. While previous studies found that VBNC H. pylori administered via gavage could cause infection in mice,19, 23 the gavage exposure method is not representative of exposure to drinking water.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations